In situ microscopy and MIR-spectroscopy as non-invasive optical sensors for cell cultivation process monitoring. (April 2014) - Lüder, Christian; Lindner, Patrick; Bulnes-Abundis, David; Lu, Shaobin M; Lücking, Tim; Solle, Dörte; Scheper, Thomas
Background: The use of modern sensors for online monitoring has become increasingly important in biotechnology. For bioprocess analysis the chemical and physical environment as well as the biological component itself must be monitored in detail and in real-time.Results: Modern non-invasive optical sensors allow reliable predictions of the current process status just in time. Two sensors, one for the biologic and one for monitoring the chemical system of a CHO cell cultivation process, are presented. With an in situ microscope, cell count and morphology are monitored, to assess the efficiency of the cell growth up to a cell concentration of 1.4·10 7 cells/ml. An infrared sensor was used to analyze glucose concentration profiles. Both sensors can be used as in situ non-invasive sensors.Conclusion: With both sensors, reliable online monitoring of CHO cell cultivation process is feasible that react immediately to changes in process conditions. Higher product quality and more efficient processes can be realized.